Impact of regulatory rules on economic performance of PV power plants. (February 2015) - Cervone, A.; Santini, E.; Teodori, S.; Romito, Donatella Zaccagnini; ,
Abstract: The rapid growth of Renewable Energy Sources (RES) power plants connected to the grid has introduced new problems related to the safe and reliable operation of the electricity network from transmission to distribution sectors. New regulatory rules can promote RES producers to make a commitment on the energy amount that is likely to be supplied to the network. The present paper concerns the analysis of the energy production of a PV power plant from the economic point of view, with reference to the presence of regulatory rules. Costs of penalty and value of energy are compared, in order to evaluate the economic efficiency of the plant. Use of auxiliary energy storage devices is investigated, with the aim to determine the relevant dimensions that increase the economic efficiency of the PV plant. A software instrument that implements these algorithms is described and applied to a case study. Highlights: Calculation support to the ESMOs for the evaluation of the economic impact on energy production of regulatory rules. Calculation support to the producers for sizing of storage ancillary systems on a maximum revenue basis. Integrated analysis of PV production, weather conditions, economic constraints on electric energy production.